Effectiveness Of Danantara Policy In Creating Golden Indonesia 2045 - Hardiansyah; Ahmad Hidayat; Bambang Amir Alhakim; Jacomina Vonny Litamahuputty; Junus Paulus Patty (Jurnal Teknologi dan Manajemen Industri Terapan, 2025)
This study is a qualitative study with a descriptive approach, namely an approach to describing in detail one by one, which is the main object of this study. The main objects that the researcher means are around Investment, Danatara, Indonesia EMAS 2045, and Effectiveness. One by one, the objects the researcher mentioned above will be described and then connected to the main topic in this study. The data used in this study is secondary data that the researcher obtained from credible sources indirectly, namely Books, Scientific Articles, Magazines, and various other sources commonly used in each study. The researcher's sources were analysed using data collection, reduction, selection, and conclusion stages. The result in this article shows that the understanding of the effectiveness of utilising all available infrastructure to achieve a desired goal, the presence of Danatara, can help achieve that goal, namely Indonesia EMAS 2045. The demographic bonus and industrialisation targeted in 2045 must be slowly supported by policies that support them. Suppose Danatara can utilise Dividends from the 7 BUMN assets mentioned above to support government policies related to industrialisation and creating the EMAS 2045 generation. In that case, the presence of Danatara can certainly help create Indonesia EMAS 2045. If, on the contrary, Danatara cannot utilise Dividends from the 7 BUMN assets, then the presence of Danatara can hinder the creation of Indonesia EMAS 2045. To solve this problem, the researcher proposes that Danatara have its own more specific master plan to help create Indonesia EMAS 2045. In addition, Danatara must also have a strict supervisor to avoid the creation of collusion, corruption, and nepotism practices in Danatara.